Characterization and anti-staphylococcal activity of the essential oil from Turnera subulata Sm. - M.G. Fernandes; R.A. Gomes; S.G. Brito-Filho; R.N. Silva-Filho; M.F. Agra; V.S. Falcão-Silva; J.P. Siqueira-Junior; M.A.R. Vieira; M.O.M. Marques; M.F.V. Souza (Universidade Estadual Paulista, 2014)
The present study is pioneer in analyzing the chemical composition of the essential oil from aerial parts of Turnera subulata Sm. and evaluates their antibacterial activity against a panel of drug-resistant strains of Staphylococcus aureus. The aerial parts were kiln-dried and then powdered in mechanical mill, and was subjected to hydrodistillation in a Clevenger-type apparatus. The components were analyzed using a mass spectrometrycoupled gas chromatography (GC-MS), and the identification of substances was performed by comparison of the mass spectra obtained with the mass spectra of the database of the GC-MS and retention indices . The essential oil was evaluated using the method of broth dilution at concentrations ranging from 3.125µg/mL to 3200µg/mL. It was possible to identify 45 substances (92.1%) of the essential oils, and the major components were trans-caryophyllene (6.7%), citronellol (5.6%), sphatulenol (5.3%), α-cadinol (4.3%), n-tricosano (4.3%), geraniol (4.1%) and trans-geranilacetone (3.7%), n-pentacosano (3.5%), globulol (3.4%), caryophyllene oxide (3.2%). The essential oil of T. subulata Sm. showed effective antibacterial activity for the various strains of S. aureus tested, with the MIC values between 25 µg/mL and 1600 µg/mL. The study of the essential oil of Turnera subulata Sm. showed that it consists of a complex mixture of several classes of compounds having the sesquiterpenes as major constituents followed by monoterpenes, and showed an antibacterial activity significant front the strains tested.